Mammary extracellular matrix directs differentiation of testicular and embryonic stem cells to form functional mammary glands in vivo - Bruno, Robert D. (Sci Rep, 2017)
Previously, we demonstrated the ability of the normal mammary microenvironment (niche) to direct non-mammary cells including testicular and embryonic stem cells (ESCs) to adopt a mammary epithelial cell (MEC) fate. These studies relied upon the interaction of transplanted normal MECs with non-mammary cells within the mammary fat-pads of recipient mice that had their endogenous epithelium removed. Here, we tested whether acellular mammary extracellular matrix (mECM) preparations are sufficient to direct differentiation of testicular-derived cells and ESCs to form functional mammary epithelial trees in vivo. We found that mECMs isolated from adult mice and rats were sufficient to redirect testicular derived cells to produce normal mammary epithelial trees within epithelial divested mouse mammary fat-pads. Conversely, ECMs isolated from omental fat and lung did not redirect testicular cells to a MEC fate, indicating the necessity of tissue specific components of the mECM. mECM preparations also completely inhibited teratoma formation from ESC inoculations. Further, a phenotypically normal ductal outgrowth resulted from a single inoculation of ESCs and mECM. To the best of our knowledge, this is the first demonstration of a tissue specific ECM driving differentiation of cells to form a functional tissue in vivo.